Right-ear precedence and vocal emotion contagion: The role of the left hemisphere. Issue 3 (4th May 2018) - Schepman, Astrid; Rodway, Paul; Cornmell, Louise; Smith, Bethany; de Sa, Sabrina Lauren; Borwick, Ciara; Belfon-Thompson, Elisha
ABSTRACT: Much evidence suggests that the processing of emotions is lateralized to the right hemisphere of the brain. However, under some circumstances the left hemisphere might play a role, particularly for positive emotions and emotional experiences. We explored whether emotion contagion was right-lateralized, lateralized valence-specifically, or potentially left-lateralized. In two experiments, right-handed female listeners rated to what extent emotionally intoned pseudo-sentences evoked target emotions in them. These sound stimuli had a 7 ms ear lead in the left or right channel, leading to stronger stimulation of the contralateral hemisphere. In both experiments, the results revealed that right ear lead stimuli received subtly but significantly higher evocation scores, suggesting a left hemisphere dominance for emotion contagion. A control experiment using an emotion identification task showed no effect of ear lead. The findings are discussed in relation to prior findings that have linked the processing of emotional prosody to left-hemisphere brain regions that regulate emotions, control orofacial musculature, are involved in affective empathy processing areas, or have an affinity for processing emotions socially. Future work is needed to eliminate alternative interpretations and understand the mechanisms involved. Our novel binaural asynchrony method may be useful in future work in auditory laterality.